PENGUATAN FUNGSI PENGAWASAN OLEH DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) TERHADAP EFEKTIFITAS PERATURAN DAERAH - Kusumah, Riva Rachmi; Siregar, Syamsul Bahri (Yustitia, 2022)
Local People's Representative Council (DPRD) In Local Government Legislation and Regional Legislative Institutions. One of the most esential issues of democracy’s results in Indonesian constitutional platform is the local legislature, so popularly known as the LocalPeople's Representative Council (DPRD). The key of the success in organizing local government is the capability of the Local People's Representative Council (DPRD) in conducting the three basic functions and plus, namely legislating, budgeting, supervising, and plus representing, simultaneously, proportionally and continously. In the future times, it is urgent to strengthen the structure and institutional capacity of the Local People's Representative Council (DPRD) by means of three agenda, that is (i) to redefine and toconsolidate the position of the Local People's Representative Council (DPRD) as a legislature; (ii) to reinforce the authority of the Local People's Representative Council (DPRD); and (iii) to maximize the capacity of the Local People's Representative Council (DPRD) in performing its all functions. To that end, it is urgent to take an effort in revising Law of 32/2004 and Law of 27/2009. "